2020
DOI: 10.1177/2040622320962648
|View full text |Cite
|
Sign up to set email alerts
|

Poricoic acid A as a modulator of TPH-1 expression inhibits renal fibrosis via modulating protein stability of β-catenin and β-catenin-mediated transcription

Abstract: Background: Renal fibrosis is the common feature of chronic kidney disease (CKD). However, few drugs specifically target fibrogenesis due to the lack of an effective therapeutic target. Hence, it is urgent to find a therapeutic strategy that inhibits renal fibrosis. Here, we identified that poricoic acid A (PAA) as the modulator of tryptophan hydroxylase-1 (TPH-1), the key enzyme in tryptophan metabolism, exerted potent anti-fibrotic effects in the kidney. Methods: Lentiviral vector, luciferase reporter activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…TCF/LEF Reporter Assay. TCF/LEF reporter assay was carried out by the procedures described previously [13].…”
Section: Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…TCF/LEF Reporter Assay. TCF/LEF reporter assay was carried out by the procedures described previously [13].…”
Section: Immunofluorescence Staining and Confocal Microscopymentioning
confidence: 99%
“…While the inhibition of β-catenin remarkably increases animal survival in the sepsis-induced ALI model [9], the activation of β-catenin contributes to inflammation through mediating the downstream target gene expression in ARDS/ALI [10,11]. Once triggered by Wnt ligands, the β-catenin protein is stabilized and accumulated in the cytoplasm and further translocates into the nucleus where βcatenin binds to T-cell factor/lymphoid enhancer factor (TCF/LEF) to initiate downstream target gene expression, including matrix metallopeptidase-7 (MMP-7) [12,13]. MMP-7 could increase permeability between endothelial cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Poricoic acid A is one of the main active ingredients in Poria cocos and has an excellent anti-renal fibrosis effect. In the UUO mice model, poricoic acid A reduced the activity of the Wnt/β-catenin signaling pathway by enhancing the expression of tryptophan hydroxylase-1 (TPH-1), and also inhibited renal cell injury and fibroblast activation, exerting an anti-renal fibrosis effect [ 56 ]. In addition, poricoic acid A can also inhibit renal fibrosis by activating the AMPK signaling pathway to inhibit TGF-β1/Smad3 pathway-mediated deposition of ECM and activation of myofibroblasts [ 57 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…A number of poricoic acids, such as secolanostane tetracyclic triterpenoids and lanostane tetracyclic triterpenoids isolated and identified from Poria cocos protected against renal fibrosis by regulating Wnt1/β-catenin, IκB/NF-κB, and Keap1/Nrf2 pathways ( Wang et al, 2017 ; Chen et al, 2019c ; Wang et al, 2020 ). Poricoic acid A, a major component of Poria cocos , has been demonstrated to protect against renal fibrosis ( Chen et al, 2019d ; Chen et al, 2020a ; Chen et al, 2020b ). Previous study showed that poricoic acid A ameliorated AKI-to-CKD continuum by inhibiting Smad3 phosphorylation of renal tissues in renal ischemia-reperfusion injury rats ( Chen et al, 2019e ).…”
Section: Natural Products As An Alternative Therapy Against Tubuloint...mentioning
confidence: 99%